Slim figure by the summer without "sacrifice" - Tatuzian, E. G.; Belovol, A. N.; Tkachenko, S. G. (Journal of Education, Health and Sport, 2017)
Most girls and women dream of a slim figure. They watch their food, spend a lot of time in sports halls, but they are not always happy with the result. The most "problem zones" are not in a hurry to please the result. The procedure of intralipotherapy can help, which in a short period of time will help to achieve the desired silhouette. With the help of intralipotherapy, it is possible to achieve the effect of liposuction. Therefore, the procedure can be recommended to a wide range of people.